Mengukur Ketimpangan Pembangunan Wilayah Antarprovinsi di Pulau Sumatra dan Jawa - Abd Hakim Aflaha; Zulgani .; Rosmeli .; Siti Hodijah; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to (1) analyse the level of development inequality between provinces in Sumatra and Java. The study uses secondary data obtained from Statistics Indonesia. The results show that North Sumatra, South Sumatra, and Riau Islands are classified as having high inequality, while Aceh, Riau, Jambi, and Bengkulu are classified as having moderate inequality, and West Sumatra, Lampung, and Bangka Belitung Islands are classified as having low inequality. In general, inequality on the island of Sumatra is classified as moderate, while on the island of Java it is classified as high due to economic concentration in industrial areas such as Jakarta and East Java